Obtention and preliminary clinical evaluation of an equine albumin for intravenous administration in adult Colombian Creole Horses (Equus ferus caballus) - Vanessa Cifuentes; Angélica Maria Zuluaga-Cabrera; Leidy Johana Vargas-Muñoz; Sebastián Estrada-Gómez (PLoS ONE, 2026)
Albumin is one of the most abundant and physiologically important blood protein in horses due to its ability to regulate vascular volume and transport blood metabolites or drugs. Despite the importance of this protein, in Colombia there is no previous reference of the use of equine albumin in horses as a pharmacological therapy and there is no available any pharmaceutical preparation of this protein to be administrated in horses. This study aims to evaluate for first time the preliminary clinical response of healthy adult Colombian Creole horses after the intravenous administration of an equine albumin preparation, manufactured in Colombia. Equine albumin was prepared from the plasma of healthy horses and obtained through the modified Salting Out technique. The Standard Quality Characterization was carried out following World Health Organization standards which included physicochemical, sterility and hemotropics tests before being administered to the horses. Albumin was administered at a concentration of 5,334 mg per animal to 3 healthy horses that were clinically evaluated before, during and after albumin administration, recording different paraclinical and clinical parameters. After manufacturing, the equine albumin obtained fulfilled the quality characteristics to be administered intravenously. After the administration, the product did not generate any adverse reactions or adverse clinical alteration at the concentration used. During the clinical evaluation we were able to observe a plasma volume expansion. Results indicates the ability to obtain a high quality product that can potentially be used as a pharmacological therapy in horses.